Pengaruh Suhu Dan Persen Katalis Zeolit Terhadap Yield Pirolisis Limbah Plastik Polypropylene (PP) - M.T. Abdul Rahman; Syarfi Daud; Muhammad Reza (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Increasing population growth leads to increased plastic waste resulting in adverse environmental impacts, If not further processed. This research was conducted to convert plastic waste into fuel oil using synthetic zeolite catalyst. The purpose of this research is to see the influence of temperature variation and percent catalyst / plastic. A total of 100 grams of polypropylene plastic type were crushed in a batch reactor at a temperature of 300 ° C, 350 ° C, and 400 ° C for 60 minutes with percent catalyst / plastic variations 5; 6; 7 (% weight). The highest yield was obtained at 400 ° C with 7% catalyst / plastic percent of 75.69%. While the highest yield without catalyst was obtained at 400 ° C at 65.57%. The product result obtained is density 0,87 gr / ml, kinematic viscosity value 2,140 cSt, flash point value 52 ° C, calorific value 44.673 kJ / kg. The analysis results show that (%) yield of the product meets the diesel (solar) standard.Keywords: liquid fuel, heating value, pyrolysis, polypropylene, synthetic zeolite.